2012
DOI: 10.1002/ange.201200309
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hydrogenation of 2,4‐Disubstituted 1,5‐Benzodiazepines Using Cationic Ruthenium Diamine Catalysts: An Unusual Achiral Counteranion Induced Reversal of Enantioselectivity

Abstract: Die hoch enantioselektive Hydrierung von 2,4‐disubstituierten 1,5‐Benzodiazepinen mit den chiralen kationischen Ruthenium‐Diamin‐Katalysatoren (R,R)‐1 (siehe Schema; BArF=Tetrakis(3,5‐bistrifluormethylphenyl)borat) kann mit einem Enantiomer des Liganden gezielt beide Enantiomere der 2,4‐Diaryl‐2,3,4,5‐tetrahydro‐1H‐benzodiazepin‐Produkte liefern. Entscheidend ist einzig das achirale Gegenion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 96 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…It is obvious that the function of the NH moiety in the ligand shown in Scheme is different from that observed in the ketone hydrogenation (Scheme ). The involvement of the interaction between the NH moiety and the counteranion X − was further shown by 45 ‐catalyzed asymmetric hydrogenation of 1,5‐benzodiazepines 36i. Ruthenium complexes 45 with weakly coordinating anions, such as BArF − , gave R , R ‐products, whereas the catalysts with hydrogen‐bond‐forming anions, such as OTf − and (PhO) 2 PO 2 − induced S , S ‐configuration.…”
Section: Mnh Catalysismentioning
confidence: 96%
See 2 more Smart Citations
“…It is obvious that the function of the NH moiety in the ligand shown in Scheme is different from that observed in the ketone hydrogenation (Scheme ). The involvement of the interaction between the NH moiety and the counteranion X − was further shown by 45 ‐catalyzed asymmetric hydrogenation of 1,5‐benzodiazepines 36i. Ruthenium complexes 45 with weakly coordinating anions, such as BArF − , gave R , R ‐products, whereas the catalysts with hydrogen‐bond‐forming anions, such as OTf − and (PhO) 2 PO 2 − induced S , S ‐configuration.…”
Section: Mnh Catalysismentioning
confidence: 96%
“…Recently, Fan and co‐workers demonstrated that η 6 ‐arene/TsDPEN‐Ru II complexes, such as 43 b , 44 , and 45 , were outstanding catalysts for asymmetric hydrogenation of 2‐substituted and 2,3‐disubstituted quinolines,36a,b,d,e 2‐substituted and 2,3‐disubstituted quinoxalines,36f 2,4‐disubstituted 1,5‐benzodiazepines,36i N ‐alkyl ketimines,36g,j cyclic N‐ alkyl imines,36h and cyclic N ‐sulfonylimines,36c affording the corresponding biologically and chemically important chiral amines with excellent enantioselectivities in high yields (Scheme ) 37. Mechanistic studies on the hydrogenations of quinolines revealed that the reduction involves a reaction sequence of 1,4‐hydride addition, isomerization, and 1,2‐hydride addition (Scheme ) 36a,d.…”
Section: Mnh Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although the reduced products represent an important class of chiral heterocycles with pharmacological activity, highly stereoselective reduction of such substrates remains a challenge. 38 Gratifyingly, these dendritic Ir-catalysts exhibited considerable enhancement in activity (Figure 7). In addition, excellent enantioselectivities and good diastereoselectivities, which comparable to those obtained with the small parent catalyst, were achieved by using a dendritic Ir/3c catalyst(Figure 8).…”
Section: Dendritic Phoxmentioning
confidence: 92%
“…Despite the successful application of asymmetric catalysis to the preparation of a single enantiomer with a certain chiral catalyst, the strategies involving enantiodivergent catalysis that enable dual or reversible enantiocontrol still remain an unexpected and significant challenge. Recently, on the basis of the same chiral ligands or catalysts, great progress has been made by several groups in this context,3–10 for example, reversal of enantioselectivity has been realized by tuning the conformational flexibility of chiral catalysts in asymmetric Michael reaction,3 the addition of zinc metal to an iron complex in the asymmetric hydrosilylation of ketones,4 the use of different metal salt catalysts,5 achiral counteranion‐induced reversal of enantioselectivity in ruthenium‐catalyzed hydrogenation,6 achiral acid‐ or base‐induced switch in the organocatalytic aldol and Mannich reactions,7 chiral anion‐dependent inversion in ruthenium‐catalyzed hydrohydroxyalkylation,8 temperature‐dependent reversal of enantioselectivity in the hydroformylation of styrene,9 and others 10…”
Section: Methodsmentioning
confidence: 99%